2010
DOI: 10.1007/s10856-010-3998-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of folic acid modified carboxymethyl chitosan nanoparticles loaded with doxorubicin for targeted delivery

Abstract: The development of smart targeted nanoparticle that can deliver drugs to direct cancer cells, introduces better efficacy and lower toxicity for treatment. We report the development and characterizations of pH-sensitive carboxymethyl chitosan modified folic acid nanoparticles and manifest their feasibility as an effective targeted drug delivery vehicle. The nanoparticles have been synthesized from carboxymethyl chitosan with covalently bonded bifunctional 2,2'-(ethylenedioxy)-bis-(ethylamine) (EDBE) through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 34 publications
3
77
0
Order By: Relevance
“…These distinctive bands of free NAR are also present in NARNS, which indicates the chemical stability of NAR in nanosuspensions [42,43].…”
Section: Fourier Transforms Infrared Spectroscopy (Ft-ir)mentioning
confidence: 87%
“…These distinctive bands of free NAR are also present in NARNS, which indicates the chemical stability of NAR in nanosuspensions [42,43].…”
Section: Fourier Transforms Infrared Spectroscopy (Ft-ir)mentioning
confidence: 87%
“…33 Despite the successes recorded following noncovalent method of conjugation of FA to other biomolecules or MNPs, [29][30][31][32][33][34] several work reported a superior performance following covalent methods of interactions. 4,35,36 However, the greatest challenge is meeting the requirements of specific conjugation chemistry that retains QDs biochemical activity as much as possible. Despite the superiority of covalent coupling of FA to QDs by means of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide-based chemistry, some researchers reported that 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide has short half-life in water and results in poor coupling efficiency.…”
mentioning
confidence: 99%
“…Targeted delivery of drugs through covalent binding of carboxymethylchitosan nanoparticles and folic acid was recently found to be possible. It was assumed that the latter would assist penetration of the nanoparticle into the cell and cause its apoptosis [4].The present communication reports the synthesis of the conjugate of a bisphosphonate derivative and folic acid. A one-step synthesis using the structural synthetic building block 1-(2-aminoethylamino)-1-(diethylphosphoryl)ethylphosphonic acid diethyl ester (2) (4) was 20%.…”
mentioning
confidence: 90%
“…Targeted delivery of drugs through covalent binding of carboxymethylchitosan nanoparticles and folic acid was recently found to be possible. It was assumed that the latter would assist penetration of the nanoparticle into the cell and cause its apoptosis [4].…”
mentioning
confidence: 99%